Visualizing Severity of Alopecia Tool (SALT) scores in the clinical setting using patient images from a clinical trial - Natasha Atanaskova Mesinkovska; Brett A. King; Sergio Vañó‐Galván; Yutaka Shimomura; Jakub Jedynak; Jill McCollam; Evangeline Pierce; Amy K. Ellinwood; Rodney Sinclair (Wiley, 2024)
Abstract Background The Severity of Alopecia Tool (SALT) is a standardized method for quantifying scalp hair loss in alopecia areata (AA). SALT scores can be used to guide treatment decisions and are widely used as eligibility criteria and endpoints for clinical trials in AA. However, clinicians may be unfamiliar with assessing and envisioning SALT scores in practice. Objectives To aid clinicians in the determination and application of SALT scores in a clinical setting, this manuscript seeks to contextualize SALT scores using patient images from a clinical trial of adults with severe AA. Methods Images from 722 patients enrolled in BRAVE‐AA1, a phase 2/3 study of baricitinib in adults with severe AA (SALT score ≥50; ≥50% scalp hair loss), were obtained at baseline and Weeks 12, 36, and 52 and compiled into a repository. Photographs were selected to represent SALT scores across the full range of disease (SALT scores 0-100) and to demonstrate the progression of SALT scores during the course of treatment. Results Images of six patients depict the range of SALT scores (0-100). Photographs are of male and female patients of different ages (21-69) and races (Asian, Black, White) with varying extent, density, and patterns of hair loss. Images of two additional patients demonstrate the use of SALT to monitor treatment progress, showing distinct patterns and timing of clinical response over 52 weeks of therapy. Conclusions The SALT is widely used in clinical trials for AA, but clinicians may lack familiarity. Presented patient images show SALT scores commonly used as eligibility criteria and endpoints in clinical trials, which may be useful in identifying patients eligible for systemic treatment and in visualizing therapeutic response.